2021
DOI: 10.3390/math9192426
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Pricing, Ordering, and Coordination for Prefabricated Building Supply Chain with Power Structure and Flexible Cap-and-Trade

Abstract: Under the increasing pressure of global emission reduction, prefabricated buildings are becoming more and more popular. As prefabricated building manufacturers and assemblers are emerging in the market, how do they make decisions of pricing, ordering, and emission reduction? In this paper, game theory is used to make the decisions for the prefabricated building supply chain with flexible cap-and-trade and different power structures, i.e., using prefabricated building manufacturers as the leader, using the vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…However, to obtain higher profits, the assembler is obliged to reasonably command the cost element. Based on game theory, Jiang et al [ 44 ] tested the two-stage prefabricated structure supply chain possessing power structures and agile cap-and-trade and explored the best strategies under tariff contracts and dissimilar power structures. Taking advantage of a Stackelberg model, Jiang and Yuan [ 45 ] considered the collaboration in the supply chain of prefabricated buildings under the cap-and-trade ordinance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, to obtain higher profits, the assembler is obliged to reasonably command the cost element. Based on game theory, Jiang et al [ 44 ] tested the two-stage prefabricated structure supply chain possessing power structures and agile cap-and-trade and explored the best strategies under tariff contracts and dissimilar power structures. Taking advantage of a Stackelberg model, Jiang and Yuan [ 45 ] considered the collaboration in the supply chain of prefabricated buildings under the cap-and-trade ordinance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding other influencing factors, Refs. [18,19] suggested that consumer low-carbon awareness has a positive effect on CER and supply chain performance.…”
Section: Cer In the Cmsc Under The Candt Mechanismmentioning
confidence: 99%
“…Liu and Li studied the use of IoT in the PBSC for promotional purposes and found that market penetration of IoT platforms in the market of primary commodities and services is a key factor influencing the decisions of key stakeholders [11]. In terms of operational decisions, Jiang et al examined the optimal pricing and ordering decisions of PBSCs under different power structures and carbon trading policies, and analyzed the impact of two-part tariff contracts on the optimal decisions [19]. Zhai et al explored the time coordination problem of PBSCs and proposed reducing the handling cost by reducing the time uncertainty and congestion probability through a spatial-temporal approach [20].…”
Section: Prefabricated Building Supply Chainmentioning
confidence: 99%